Probing English Language Learning Challenges among University Students in Suburban Town Settings - Areen Ahmed Muhammed (Zanco Journal of Humanity Sciences)
Despite 12 years of English education, Kurdish university students, particularly those living in suburban towns, face persistent challenges in learning a foreign language, hindering their academic aspirations. This study focuses on students who live in Chamchamal and its surrounding areas and identifies key obstacles such as systemic school issues, the previous educational environment, and demotivational factors, whether from their parents or the community. This study uses a mixed-methods approach, combining surveys and interviews with students and teachers to assess English language challenges and the impact of educational environments in Chamchamal. Data collected from 30 students reveal that shyness significantly hinders language acquisition, teacher behavior affects learning outcomes, and a lack of student enthusiasm impedes progress. The study challenges claims about the impact of power dynamics and library access, offering valuable insights into the challenges faced by suburban town students in learning English. It also proposes solutions to enhance English language learning and aims to raise awareness among students' families about the issues affecting their children's acquisition of English as a foreign language. This study aims to explore the linguistic challenges faced by university students in Chamchamal, Kurdistan Region-Iraq, and offer targeted recommendations to improve their English language proficiency.